Effect of long-acting β-agonists/glucocorticoids on human airway epithelial cell cytokine, transcriptomic and oxidative stress responses to cannabis smoke. Issue 1 (20th January 2020) - Huff, Ryan D.; Aguiar, Jennifer A.; Tse, Wayne; Stämpfli, Martin R.; McConkey, Brendan J.; Doxey, Andrew C.; Hirota, Jeremy A.
Cannabis is one of the most widely consumed drugs in the world, with an estimated 180 million annual users globally [1]. Recent trends of legalisation of medicinal and/or recreational cannabis have led to increased access to cannabis products that will likely lead to increased use over the coming years. Inhalation of combusted cannabis is by far the most prevalent form of cannabis use, reported by 89% of users in the 2018 Canadian Cannabis Survey [2]. Chemically, cannabis smoke includes pharmacologically active components such as tetrahydrocannabinol (THC), cannabidiol (CBD) and polycyclic aromatic hydrocarbons [3]. Many studies have investigated the psychoactive and immunomodulatory properties of THC and CBD respectively, and examined the potential use of cannabis as an intervention for chronic pain, immune disorders and neurological disorders [4, 5]. Despite this body of knowledge and recent rise of systematic reviews on these topics, the effects of inhaled cannabis smoke on the respiratory mucosal immune responses are less clear [6]. LABA/GC intervention in airway epithelial cells exposed to cannabis smoke reduces levels of pro-inflammatory (CXCL8) and antiviral (CXCL10) mediators, while transcriptomic signatures of neutrophil-mediated immunity and oxidative stress remain elevated http://bit.ly/2qiSQhH